PERZINAHAN DALAM PRESFEKTIF ISLAM SEBAGAI ALTERNATIF PEMBAHARUAN HUKUM PIDANA TENTANG PERZINAHAN DI INDONESIA - Hendri Nauli Rambe; Alvi Syahrin; Muhammad Hasballah Thaib; Marlina Marlina (USU LAW JOURNAL, 2016)
ABSTRACT Adultery is a criminal act in Indonesia; it is regulated in the Criminal Code as it is stipulated in Chapter XIV on Criminal Act against Morality, and specifically in Article 284 on Adultery. But law on adultery in the Criminal Code is different from that in fiqh finayah in Islam because there is the difference in committing adultery, responsibility, and legal aid for adulterers in the two systems.The result of the research shows that adultery stipulated in the Criminal Code was incorrect since it implies that adultery will impose the sanction only on those who are married and the punishment does not have any cured effect for the perpetrators. On the other hand, the Islamic law will punish those who are married and single and imposes ‘hudud’ for the perpetrators. Indonesia that is based on religion and the majority of its people are Moslems should carry out religious sharia completely. The Islamic law can be used as an alternative for the innovation of the criminal law about adultery in Indonesia that does not respect moral and religion.It is recommended that law makers, especially those who draft the Bill of the Criminal Code on indecent assault, should pay attention and consider religious and cultural values in society, and the Indonesian citizens should give values and understanding about religion in families. Keywords: Adultery, Islamic Law, Innovation of the Criminal Law